EDUCATIONAL TRAINING BUILDING CREATIVITY AND INDEPENDENCE FOR STUDENTS OF SMKN 1 IDI, EAST ACEH DISTRICT - Esti Alemia Puspita; Cut Eva Wani; Wiriani, Erni (Yayasan Putra Adi Dharma, 2024)
This activities was entitled Education and Training to Build Creativity and Independence of SMKN 1 IDI. The purpose of this service is to provide direction and guidance to SMKN 1 IDI, in terms of developing creativity and independence in order to develop their potential. The method of implementing this service is carried out in several stages, namely. 1) Preliminary stages; This stage includes field survey activities and relationships with the object of the service location as well as the preparation of activity designs and outputs from these activities. 2) Socialization Stages; in this stage the team that has compiled and formed the program design then submits it to the school and the implementation and the specified outputs. 3) Stages of implementation; this stage is the implementation of the activity design that has been determined. The conclusion of this service is that students are enthusiastic about carrying out activities that are in self-development so as to generate creativity and independence which ultimately leads to entrepreneurship. The hope of this service activity is that it can open students' insights so that they can further develop themselves, especially in terms of creativity and learning independence. So that it will be able to have an impact both in the family environment, school or community environment in general